Knock‐in of P301L tau homolog in Drosophila leads to neuronal loss and widespread neurodegeneration. (20th December 2022) - Bukhari, Hassan; Feany, Mel
Abstract: Background: Mutations in tau protein, such as P301L, play an important role in the pathogenesis of Alzheimer's disease and frontotemporal dementia. A knock‐in of P301L tau homolog in Drosophila led to extensive neuronal loss and widespread neurodegeneration. Method: The human P301L tau homolog in Drosophila, P251L tau, was knocked in by using CRISPR/Cas9 gene editing. Markers of neurodegeneration were quantified by immunostaining. Mitochondrial bioenergetics was quantified by a seahorse analyzer. Single‐cell RNA sequencing analysis was done on the 10 days old P251L tau and control Drosophila brains. Result: The results show that the P251L tau Drosophila brain shows an age‐dependent increase in DNA damage compared to the control. Other markers of neurodegeneration such as vacuolation, proliferating cell nuclear antigen (PCNA) and tau inclusion bodies were also found to be elevated in the tau P251L Drosophila brain. Furthermore, a decrease in mitochondrial bioenergetics, oxygen consumption rate, and extracellular acidification rate was also found in the P251L tau compared to the control Drosophila brain. Conclusion: The CRISPR/Cas9 mediated knock‐in of human P301L tau homolog in Drosophila leads to extensive neuronal loss and widespread neurodegeneration.